Pest categorisation of Stenocarpella maydis. (24th November 2022) - ,; Bragard, Claude; Baptista, Paula; Chatzivassiliou, Elisavet; Di Serio, Francesco; Gonthier, Paolo; Miret, Josep Anton Jaques; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; et al.
Abstract: The EFSA Plant Health Panel performed a pest categorisation of Stenocarpella maydis, a clearly defined fungus causing seedling blight, stalk and ear rot in maize, its only confirmed main host. The pathogen occurs in many countries of North, Central and South America, Africa, Asia and Oceania where maize is grown commercially. It is present in the EU with restricted distribution (Czech Republic and Spain). Stenocarpella maydis is not included in Commission Implementing Regulation (EU) 2019/2072. Plants for planting (maize seeds) is the main pathway of entry and spread in the EU. Host availability and climate are favourable for the establishment of the pathogen in maize‐growing areas of the EU. The pathogen has a direct impact on yield and quality of maize production. Phytosanitary measures are available to mitigate further introduction and spread of the pathogen into the EU. The Panel concludes that S. maydis satisfies all the criteria to be regarded as a potential Union quarantine pest.